218k views
3 votes
What are the solutions to the equation (x-6)(X + 8) = 0?

O x=-6 or x = 8
O x=-6 or x = -8
O x= 6 or x = -8
O x = 6 or x = 8

What are the solutions to the equation (x-6)(X + 8) = 0? O x=-6 or x = 8 O x=-6 or-example-1
User Jbatista
by
4.5k points

1 Answer

1 vote

Answer:

The correct option is C....

Explanation:

First of all multiply the terms:

(x-6)(x+8)=0

x^2+8x-6x-48=0

Now solve the like terms:

x^2+2x-48=0

Now we will solve this quadratic equation by factoring:

The first terms has coefficient 1. So 1 will be multiplied by the constant term 48.

1*48= 48

Now we have to find out the two values whose product is 48 and whose sum or difference is 2(middle term).

8*6 = 48

8-6 = 2

Now break the middle term:

x^2+8x-6x-48 = 0

Now take the common from the first two and last two terms:

x(x+8)-6(x+8) = 0

(x+8)(x-6)=0

x+8=0 , x-6=0

x= 0-8 , x=0+6

x = -8 , x=6

Thus the solutions we get are: x=6 or x= -8

The correct option is C....

User Mattia Durli
by
5.0k points